Hubungan psychological capital dengan komitmen organisasi pada aparatur sipil negara - Gustina Anggraini (Fakultas Psikologi, 2021)
Organizational commitment is the willingness of members to have a relationship with the organization. High organizational commitment will lead to high on aspects like performance, discipline and achievement. A positive psychological state must be possessed because it can affect organizational commitment. Psychological capital is a developmental condition of a person’s positive psychological state and the emergence of self-efficacy, hope, resilience, and optimism so that it is related to organizational commitment. The purpose of the study was to determine the relationship between psychological capital and organizational commitment in ASN samples. Quantitative research in design and the data gathered from 125 ASN participants with at least one year of working experience in an organization or agency. Data were collected using psychological capital (PCQ) and organizational commitment scale (OCQ). Hypothesis testing was carried out with Pearson’s product moment correlation using SPSS. The results showed that there was a positive relationship between psychological capital and organizational commitment in state civil apparatus (r=0.87, p=0.000). It means the higher the psychological capital, the higher the organizational commitment. Keywords: Organizational commitment, psychological capital, state civil apparatus